Ecuadorian teachers communication: Presence and use of academic scientific networks [Docentes ecuatorianos de comunicación: Presencia y uso de las redes científicas académicas] - Punin Larrea, M. (2016)
This article analyzes the quantitative presence of teachers from the faculties of communication of Ecuador accredited by the state in category A and B, within the academic scientific networks Academia. edu, Researchgate. net and open profile associated with Google Scholar. Identifies the number of followers and accounts following researchers, events that are attributed to each of them, in order to measure the impact and spread scientific networks provoking study. The results place the Technical University of Loja (UTPL-Loja), the Polytechnic School of the Coast (ESPOLGuayaquil) and the Central University of Ecuador (UCE-Quito) and institutions with greater presence within the academic scientific networks; also it concluded that the continual use of profiles is irrelevant and is still in consolidation.